Prospects for involvement in the criminal procedural evidence of "biometric data" - Mikhailishina A. A. (Topical issues of law, economic and management, 2020)
Despite the prevalence of crimes committed with the help of technical devices, the procedural procedure for removing and fixing traces left as a result of cybercrimes and other crimes is not sufficiently specified. The growth of cybercrime is directly related to the availability and popularity of digital technology, and to disclose these crimes, first of all, use new sources of evidence.
Keywords: современные технологии; доказательства; evidence; киберпреступность; биометрические данные; biometric data; cybercrime; modern technology; personal identification; идентификация личности